Synthesis and characterization of Au/ZnO/Cu thin film memristor - Marmeezee Mohd. Yusoff (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The resistive switching characteristics between a high resistance state (HRS) and a low resistance state (LRS) of a memristor exhibit memory effect behaviour. This phenomenon has been reported in transition metal oxide (TMO) materials. Zinc oxide (ZnO), for instance, has been reported as an important semiconductor material for applications in electronic devices. This master thesis employed ZnO as a memristive medium for its advantages over other semi-conducting TMOs. For the purpose of fabrication, ZnO films were deposited on copper (Cu) substrate using electro-deposition and thermal oxidation methods. The effect of deposition time and concentration of ZnCl2 solution was investigated and discussed. Synthesized ZnO films were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and electrical measurement. The XRD and FESEM characterization results showed that ZnO nanoparticles were successfully synthesized on Cu substrate. The deposition time and concentration of ZnCl2 solution determine the resistive property of the oxide. The thicknesses also were observed to increase in proportion to the depositing time and concentration of ZnCl2 solution. The results from electrical measurements showed that the deposited ZnO exhibits pinched hysteresis behaviour as apparent from the I–V curves. It is observed that the maximum and minimum currents gained at the particular maximum and minimum voltages decreased with the increase in deposition time and concentration of ZnCl2 solution. The pinched hysteresis loops also show that increasing of these two parameters increase the resistance of the memristor device, and decrease the difference between high resistance state (HRS) and low resistance state (LRS), represented by Δ Imax of the synthesized ZnO thin film. The largest HRS-LRS obtained from the experiments conducted was 14.11 kΩ with an associated resistance switching ratio, Roff/Ron, of approximately 4.0. It is therefore concluded that the deposition time and concentration of ZnCl2 solution played a significant role in increasing the performance of the memristive device. Thus, the synthesized ZnO shows potential for use in the production and application of non-complex and low cost memristors.